Detention of Refugee Children in Malaysia and Thailand - Samitra Parthiban; Khoo Ying Hooi (Jember University Press, 2019)
The refugee issue in Malaysia and Thailand is one of the most protracted human rights issues that both countries face. Regardless of abundant requests and advocacies by non-state actors, both locally and internationally, to persuade the governments of Thailand and Malaysia to provide protection to refugees, the fate of these refugees remain uncertain. One of the key limitations for the human rights protection of the refugees is that both countries did not sign the 1951 Refugee Convention or its 1967 Protocol, moreover, both Thailand and Malaysia do not treat the refugee issue as a domestic problem. This paper examines the detention of refugee children in Malaysia and Thailand with the main intention to advocate for the method of Alternatives to Detention (ATD) as a solution to the shortcomings in a legal method. Based on that, this paper first explores the human rights situation of refugee children in detentions by looking into the current detention practices of both countries. Secondly, this paper examines the strategies and tactics of how the local Non-Governmental Organizations (NGOs) advocate and convince their governments to adopt the approach of ATD.